Novel Technique Of Modal Analysis For Light Structure Via Piezofilm Sensor: A Comparison Study - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Abdullah, Shahrum; Mohammad Rasani, Mohammad Rasidi; Kho, Ko Seng; Ahmad, Muhamad Arif Fadli (Penerbit UTM Press, 2017)
This study is conducted to determine the modal parameters namely natural frequencies and mode shapes of aluminum 6061 (Al6061). A light and small structure made from Al6061 is chosen as the experimental specimen mainly because of its wide application in industries such as automotive parts or accessories and robotic, mainly in manufacturing of automobile frames. If a component vibrates with a frequency that is coherent with the component’s natural frequency, resonance frequency will occur and structural failure might emerge. Two sensors i.e. piezoelectric film and accelerometer were used. The result obtained were ya = 329.60x – 142.27 (accelerometer) and yp = 304.98x + 15.18 (piezofilm). The relation between natural frequency of accelerometer and piezofilm for the triangle-shape specimen was ya = 1.08yp – 158.67 and can be concluded that the regression ratio of 1.08 was approximately 1.0 which agreed with the status of piezoelectric film sensor that can be used as an alternative sensor for accelerometer. There was a good results agreement between simulation and experimental work outcome.